2013
DOI: 10.1093/qje/qjt057
|View full text |Cite
|
Sign up to set email alerts
|

Generating Skilled Self-Employment in Developing Countries: Experimental Evidence from Uganda *

Abstract: We study a government program in Uganda designed to help the poor and unemployed become self-employed artisans. The program targeted people ages 16 to 35 in Uganda's conflict-affected north, inviting them to form groups and submit grant proposals to pay for vocational training and business start-up. Funding was randomly assigned, and treatment groups received unsupervised cash grants of $382 per member on average. The government's main aims were to increase incomes and thus also promote social stability. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(108 citation statements)
references
References 39 publications
5
102
0
1
Order By: Relevance
“…Furthermore, the program had no discernible impact on social networks, relationships with former commanders, aggression, or social integration. As in the previous studies ( [8], [9]), this study found that the program had no impact on attitudes toward the use of violence or democracy [10].…”
Section: The Causal Relationship Between Violence and Unemploymentsupporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, the program had no discernible impact on social networks, relationships with former commanders, aggression, or social integration. As in the previous studies ( [8], [9]), this study found that the program had no impact on attitudes toward the use of violence or democracy [10].…”
Section: The Causal Relationship Between Violence and Unemploymentsupporting
confidence: 77%
“…Another study provides a more recent randomized study of an employment project in Uganda [9]. The program provided vocational training and business start-up grants to randomly selected youth in a conflicted area in Uganda.…”
Section: The Causal Relationship Between Violence and Unemploymentmentioning
confidence: 99%
“…This is the case with work testing small grants of US$100 to US$200 to existing businesses (e.g., De Mel, McKenzie, and Woodruff 2008;McKenzie and Woodruff 2008;Fafchamps et al 2014;Karlan, Knight, and Udry 2015); ultra-poor programs providing grants and training to get very poor people to start businesses (e.g., Banerjee et al 2015;Bandiera et al 2017); and business training programs for microenterprises (reviewed in McKenzie and Woodruff 2014). Blattman, Fiala, and Martinez (2014) considers a program in Uganda where groups received grants of approximately US$382 per member, and finds this generates increases in skilled self-employment and in incomes for the recipients, but only minor increases in employment in these firms. Fafchamps and Quinn (forthcoming) provide grants of US$1,000 to their 39 winners.…”
mentioning
confidence: 99%
“…The need for group members to make collective decisions contributed to the success of the program. After four years, the incomes of participating women were 73% greater than the incomes of the control group; for men, the differential gain was 29% [8]. This study is a rare example of a longer-term (after four years) evaluation of a government program to ease the transition from agricultural employment to artisanal activities.…”
Section: Status In Employmentmentioning
confidence: 83%